Why do women engage in fat talk? Examining fat talk using Self-Determination Theory as an explanatory framework. (March 2017) - Guertin, Camille; Barbeau, Kheana; Pelletier, Luc; Martinelli, Gabrielle
Highlights: Fat talk was examined using Self-Determination Theory. Two processes to eating regulation, based on motivation and goals, were examined. Non-self-determined motivation and appearance goals were linked to fat talk. Fat talk was linked to a maladaptive style of eating and in turn, unhealthy eating. Self-determined motivation and health goals were not associated with fat talk. Abstract: This study used Self-Determination Theory to examine the motivational processes involved in individuals' engagement in fat talk and its association with unhealthy eating behaviors. Female undergraduate students ( N  = 453) completed an online questionnaire, which assessed general and contextual motivation, importance placed on goals, fat talk, and unhealthy eating behaviors. Structural equation modeling revealed that being generally non-self-determined and placing more importance on extrinsic goals, such as thinness, was associated with fat talk. Fat talk was further associated with non-self-determined motivation for eating regulation, which in turn was associated with unhealthy eating. General self-determination and placing more importance on intrinsic goals, such as health, were not associated with fat talk, but instead, were associated with more adaptive forms of eating regulation and diet quality. Findings further current knowledge on the respective roles of motivation and goals on the engagement in fat talk, and its consequences on eating regulation and behavior.